The Correlational Study on Cadres Knowledge and Readiness for Pregnancy Stunting Prevention - Debora Aprilia; Elvira Destin Pillo; Gita Sampe Lantang; Marianna R. G Tompunu; Melisa Constantine Sigarlaki (Indonesian Journal of Global Health Research, 2025)
Stunting is a condition of growth failure in children under five due to malnutrition, so their height is below average. Stunting incidence in Kampung Dadap in October 2023 reached 70% of cases. Data collected from Kutai Health Center states that there are 18 pregnant women, four of whom are at high risk of stunting. The number of active cadres is 69, and five are at Posyandu Dadap. During the data collection, the stunting prevention program for examining pregnant women in Kampung Dadap had not yet begun, as it is scheduled to commence in early 2024 The program that will be carried out in early 2024 is the examination for pregnant women stunting prevention. Objective: This study aimed to determine the correlation between knowledge and readiness of cadres towards implementing a pregnancy stunting prevention program in Kutai Health Center. Method: This study uses a correlational quantitative research method with a cross-sectional approach. The sample was selected using a total sampling technique where the sample size was 69 cadres. The instrument used two types of questionnaires with 30 questions that had been tested for validity and reliability. The data analysis technique uses bivariate analysis, which has been tested using the Chi-Square test. Results: This study indicates no significant relationship between knowledge level and cadres readiness (p-value = 0.702). Conclusions: Future researchers are advised to examine other variables such as length of service, motivation, and level of education, and they can expand the population and sample in the study by using several health centers as research targets.